Verbalphrase im deutschen und im polnischen Expertentext (am Beispiel philologischer Aufsätze) - Lesław Cirko (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
This paper presents the results of a corpus-based comparison of verbal phrases in German and Polish scientific texts. Describing the verb and its dependent elements is an important step-leading to better comprehension and more effective syntactic analysis of a sentence. The distribution of grammatical categories such as person, number, tense, mood and voice, will be discussed in order to show their specific functions in the scientific texts in both languages. Special attention will be paid to how different views of the world are expressed in the texts, due to the inflexion discrepancies in German and Polish tradition of academic writing.